Performance Evaluation of Delay and Jitter in Optical Fiber Networks for Real-Time Multimedia Applications - Ayu Mika Sherila; Melisa Mulyadi (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2025)
The increasing reliance on real-time services such as VoIP and video streaming underscores the critical role of fiber optic networks as high-capacity communication backbones. While optical fibers offer substantial bandwidth, this alone does not ensure optimal Quality of Experience (QoE); network delay and jitter remain prominent challenges that can disrupt audio clarity and video continuity. This paper presents a detailed analysis of delay and jitter phenomena within fiber optic systems, particularly emphasizing Passive Optical Network (PON) topologies. It explores the underlying causes of performance degradation from physical-layer limitations to architectural inefficiencies and critically assesses current mitigation techniques implemented at both the network level (e.g., Quality of Service mechanisms) and application level (e.g., jitter buffering strategies). The main contribution of this work is the introduction of a novel